2020
DOI: 10.1108/jbim-01-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Promoting desirable work attitudes and behaviors among accountants: a field study

Abstract: Purpose Accounting work is characterized by high job demands and tight deadlines. With less task variety, accounting work is susceptible to employee disengagement. This paper aims to examine the role of enhanced performance management practices as intervention mechanism to the disengagement among accountants. Design/methodology/approach A total of 105 accountants participated in an online survey, answering self and social reports. Hypotheses were tested using regression analyses. Findings Enhanced performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
3
0
2
Order By: Relevance
“…Employees will be more likely to engage in knowledge sharing behaviours if they know that they will receive rewards for doing so (Wang et al, 2014;Foss et al, 2009). For employees to be able to engage in innovative behaviours, knowledge is critical in fostering such behaviours as it helps reduce task complexities and save time (Asare, Whittington and Walsh, 2020;Scarbrough, 2003).…”
Section: Rewards Knowledge Sharing and Iwbmentioning
confidence: 99%
“…Employees will be more likely to engage in knowledge sharing behaviours if they know that they will receive rewards for doing so (Wang et al, 2014;Foss et al, 2009). For employees to be able to engage in innovative behaviours, knowledge is critical in fostering such behaviours as it helps reduce task complexities and save time (Asare, Whittington and Walsh, 2020;Scarbrough, 2003).…”
Section: Rewards Knowledge Sharing and Iwbmentioning
confidence: 99%
“…2.2 B2B implications regarding the "status" element Providing feedback information in B2B companies to the salesforce and other employees is very important part of creating effective programs centered on delivering superior customer service (Asare et al, 2020;Cina, 1989;Gummesson, 2004;Schwepker, 2016). Neuroscience research has found that "status-confirming information can elicit activation in reward neural circuitry" (Rock and Cox, 2012, p. 4).…”
Section: Implementing the Scarf Framework In Managerial B2b Practicementioning
confidence: 99%
“…Professionals continually learn from experience throughout their careers, allowing them to accumulate knowledge and reduce uncertainty (Hitt et al, 2001). However, they often face scenarios in which their knowledge is insufficient to address a specific problem, and thus may refer to external sources to access information, suggestions and feedback (Asare et al, 2020;Siahtiri et al, 2020).…”
Section: Research Backgroundmentioning
confidence: 99%